أخلاقية العولمة في القرآن الكريم: مقارنة مع أخلاقية العولمة اليوم - NAsih Ulwan, Ammar Abdullah (Journal of Al-Tamaddun, 2009)
The current study examines Islam as a universal religion, by legislate laws and rules designed to bring about an actions which make all people being dealt as one nation. It also examined people tongues speaking variety as one of the greatest Allah?s almighty signs. In the last decades, the term Globalization has come to dominate our lives, and emerged as one of the key worldwide dealing. This paper attempts to demonstrate the usefulness of globalization in Islamic thoughts as it is the best way of knowledge interchange and life experiences among nations. A clear understanding of the term of globalization would be benefited by: 1. Identifying this term comparing with actual situations overwhelming the world; 2. Globalization morality between Islamic world role and united nation ethics; 3. The concept of globalization morality in the holy Quran moral principles, comparing to it?s morality in principal issues for instance, economic and family affairs.